Taʼthīr Wasīlah Al-Kutub Al-Mujassimah Al-Mutaḥarrikah ʻalá Istīʿāb Al-Mufradāt Ladá Ṭullāb Al-Madrasah Al-Ibtidāʼīyah Al-Islāmīyah Al-Ḥukūmīyah Bukittinggi - Ayu Annisa (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The problems in this research are student's comprehension of Arabic vocabulary is low. In addition, the teacher did not use the fun and varied teaching media when teaching. The aims of this research is: 1) To find out the difference in the comprehension of Arabic vocabulary between students who learn using Pop Up Books media and students who learn using whiteboard, 2) To know the effect of the Pop Up Books media on the comprehension of Arabic vocabulary for the 3rd grade students at the Goverment Islamic Elementary School Bukittinggi. This research is experimental research means quasi-experimental by type non equivalent control grup. The population is all 3rd grade students and the sampling technique is cluster sampling. The data collection tools used are test, observation and interview. The result of the research are: 1) There is a difference in the comprehension of Arabic vocabulary between students who learn using Pop Up Books media and students who learn using whiteboard, 2) There is an effect of the Pop Up Books media on the comprehension of Arabic vocabulary for the 3rd grade students at the Goverment Islamic Elementary School Bukittinggi because in Independent Sample t-Test, the researcher obtained a score of tcount>ttable (2,257>2,009).المشكلات في هذا البحث هي استيعاب الطلاب للمفردات العربية منخفض. بالإضافة إلى ذلك، لم تستخدم المدرّسة الوسائل التعليمية الممتعة والمتنوعة عند التعليم. أهداف هذا البحث هي: 1) لمعرفة فرق استيعاب المفردات العربية بين الطلاب الذين يتعلمون باستخدام وسيلة الكتب المجسمة المتحركة (Pop Up Books) والطلاب الذين يتعلمون باستخدام السبورة، 2) لمعرفة تأثير وسيلة الكتب المجسمة المتحركة (Pop Up Books) على استيعاب المفردات العربية لدى طلاب الفصل الثالث في المدرسة الابتدائية الإسلامية الحكومية بوكيت تنجي. هذا البحث هو البحث التجريبي يعني شبه التجريبية بالنوع مجموعة الضابط غير متكافئة. والمجتمع لهذا البحث هو جميع الطلاب في الفصل الثالث وتقنية أخذ العينات هي Cluster Sampling. أدوات لجمع البيانات المستخدمة هي الاختبار والملاحظة والمقابلة. أما نتائج البحث هي: 1) يوجد فرق استيعاب المفردات العربية بين الطلاب الذين يتعلمون باستخدام وسيلة الكتب المجسمة المتحركة (Pop Up Books) والطلاب الذين يتعلمون باستخدام السبورة، 2) يوجد تأثير وسيلة الكتب المجسمة المتحركة (Pop Up Books) على استيعاب المفردات العربية لدى طلاب الفصل الثالث في المدرسة الابتدائية الإسلامية الحكومية بوكيت تنجي لأن في اختبار Independent Sampel t-Test حصلت الباحثة على درجة